2009
DOI: 10.1007/s10803-009-0832-2
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Among Adolescents With Autism Spectrum Disorders: Prevalence and Perception

Abstract: This study examined: (a) the prevalence of bullying and victimization among adolescents with ASD, (b) whether they correctly perceived bullying and victimization, and (c) whether Theory of Mind (ToM) and bullying involvement were related to this perception. Data were collected among 230 adolescents with ASD attending special education schools. We found prevalence rates of bullying and victimization between 6 and 46%, with teachers reporting significantly higher rates than peers. Furthermore, adolescents who sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
223
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(243 citation statements)
references
References 44 publications
9
223
1
10
Order By: Relevance
“…Also, Heerey et al (2005) found that teasing of individuals with autism is less playful and less good-natured than teasing of control children. Van Roekel et al (2010) reported a close relationship between being bullied and more poorly developed Theory of Mind skills. Here as well, we assume that decreased empathy and interpersonal sensitivity might be related to katagelasticism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Heerey et al (2005) found that teasing of individuals with autism is less playful and less good-natured than teasing of control children. Van Roekel et al (2010) reported a close relationship between being bullied and more poorly developed Theory of Mind skills. Here as well, we assume that decreased empathy and interpersonal sensitivity might be related to katagelasticism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these individuals have been reported to have difficulties reading non-verbal cues (Asperger 1944;Attwood 2004), which may be highly important when distinguishing good-natured teasing from mean-spirited bullying. The particular importance of Theory of Mind in the context of bullying and teasing has recently been shown by Van Roekel et al (2010), who noted that the more often adolescents are bullied, and the less developed their Theory of Mind is, the more they misinterpret bullying situations as non-bullying. However, the assumption that a distorted Theory of Mind, including difficulties reading non-verbal signs, contributes to the development of gelotophobia needs further clarification in studies that test the relationship between Theory of Mind abilities and developing a fear of being laughed at, for example, in a longitudinal design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being different, however, is often not accepted by typical adolescents (Humphrey & Lewis, 2008;Martino & Pallotta-Chiarolli, 2005), therefore these results may have implications for inclusion practices by challenging what most typical adolescents consider "normal". Given the high rates of bullying in autism (Roekel, Scholte, & Didden, 2010), with autistic adolescents reporting that encounters with peers can be frequently hostile or negative (Carrington et al, 2003b;Williamson, Craig & Slinger, 2008), teaching typical children the positives of diversity (and neurodiversity) could be one way of improving autism acceptance. Finally, this study demonstrates the importance of enabling young people on the autistic spectrum to speak out about their social experiences, in this instance by revealing new insights into reputation concerns in autism.…”
Section: Discussionmentioning
confidence: 99%
“…Cerca de 30% delas vivencia algum tipo de violência perpetrada por pares (BLAKE et al, 2012;SON et al, 2012;VAN ROEKEL et al, 2010). Pais e professores de adolescentes apresentam percepção da violência diferente da apresentada pelos jovens, uma vez que os primeiros relatam taxas ainda superiores de vitimização (CAPPADOCIA et al, 2012;STERZING et al, 2013).…”
Section: Discussionunclassified